2022
DOI: 10.3389/fpsyg.2022.742546
|View full text |Cite
|
Sign up to set email alerts
|

Leader Humility and Machiavellianism: Investigating the Effects on Followers’ Self-Interested and Prosocial Behaviors

Abstract: Existing research on leader humility primarily demonstrates its positive effects. This study challenges this view by proposing the potential negative effects of leader humility on followers’ behaviors. Furthermore, this paper employs the person-situation interactionist perspective to extend the research on integrating followers’ personality traits and leader humility. Specifically, this study proposed that leader humility triggers their followers’ sense of power; moreover, this study wagers that whether follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Another study found a negative correlation between humility, specifically the H dimension of the HEXACO personality model, and a wide array of Machiavellian behaviours such as criminal activity and power-seeking tendencies, potentially hinting at a protective social benefit related to humility 18 in the form of stronger hierarchical structures 19 . Namely, leaders with higher state and/or trait humility are less likely to make decisions that are self-serving at the expense of the group 18 , and this reinforces follower humility while acting as a protective factor against Machiavellianism in followers. This would, in turn, reduce their potentially detrimental powerseeking tendencies.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another study found a negative correlation between humility, specifically the H dimension of the HEXACO personality model, and a wide array of Machiavellian behaviours such as criminal activity and power-seeking tendencies, potentially hinting at a protective social benefit related to humility 18 in the form of stronger hierarchical structures 19 . Namely, leaders with higher state and/or trait humility are less likely to make decisions that are self-serving at the expense of the group 18 , and this reinforces follower humility while acting as a protective factor against Machiavellianism in followers. This would, in turn, reduce their potentially detrimental powerseeking tendencies.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, many scholars also proposed that followers are a very important factor in the effectiveness of leadership. In the relevant research on the interaction between leadership and followership, there have been studies to explore the relationship between leadership styles and followers' characteristics [12,13]; leader and follower interactions; the relations with OCB and sales productivity [24]; about how the interaction between transformational leadership and followers affects the engagement contribution of subordinates [64].…”
Section: The Relationship Among Olif Trust In Supervisor Ocb and Acti...mentioning
confidence: 99%
“…Many existing studies have explored variable leadership and followership behavior and have also confirmed that leaders and followers have an interactive relationship with each other's behavior [5,11]. More recent studies have highlighted follower behavior resulting from the interaction between leader and follower behavior [12,13] such as leadership and trust in supervisor [14,15]; leadership and organizational citizenship behavior [16,17]; trust and organizational citizenship behavior [18,19]. Meindl (1995) proposed a follower-centric perspective in his study, which pointed out that leaders and their leadership results are constructed by followers [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation